Analisis Studi Literatur Meningkatkan Kemampuan Pemecahan Masalah Computational Thinking Pada Siswa Madrasah Ibtidaiyah - Desmi Fitri Syahdani Br Sitepu; Yahfizham Yahfizham (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This literature study analysis discusses improving computational thinking problem solving abilities in madrasah ibtidaiyah students. In this study, an analysis of various literature that has been carried out previously was carried out to understand how the use of computational thinking can improve problem solving abilities in madrasah ibtidaiyah students. One of the journals that is relevant to this topic is "Computational Thinking in Madrasah Tsanawiyah Maulana Maghribi Kandeman Students in Improving Problem Solving Abilities" which was published in the journal Circle: Journal of Mathematics Education. This journal was written by Muhammad Nur Fain Syamsy and A. Sholikhah on September 28 2023. This study explores how the application of computational thinking can help students solve problems. The research results show that students who are involved in learning computational thinking have better problem solving abilities. Apart from that, other relevant research is research conducted by Kurnadi et al. (2021) which concerns the introduction of computational thinking to students at Madrasah Ibtidaiyah Nahdlatul Wathan Marcapada West Lombok. This research also shows that learning computational thinking can improve students' problem solving abilities. In this research, the use of literature study analysis methods is important to gain a deep understanding of the influence of computational thinking on problem-solving abilities in madrasah ibtidaiyah students. By studying existing literature, researchers can identify the best approaches and strategies in developing students' problem solving abilities.